(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This research paper has been elevated with the homocysteine atherosclerosis promoted through the stress-increased oxidant, impaired with an endothelial function as well as thrombosis of induction. It is also increasing the role within the HMG activity Co A reductase that can turn cholesterol increases synthesis. It is increased with the cholesterol-promoted level of atherosclerosis as well as since it is such a risk factor in CAD. the levels of serum homocysteine where it was found significantly higher in CAD and it is with than the no subjects of CAD. The high homocysteine levels have damaged the inside that increasing as well as arteries' risk of blood-forming clots. It can increase with the heart attack risk, stroke, and some other diseases of the heart as well as blood disorders vessel. High homocysteine levels can increase the blood LDL cholesterol, which can be associated with damage in arteries lining as well as atherosclerosis narrowing of arteries as well as hardening. Hcy considered concentration as a factor of risk for cardiovascular disease as well as it can be also associated with hypertension. it is such as diagnosed with invasiveness with acetylcholine testing provocation, and even it is after adjusting with the risk of cardiovascular covariables.